A Rare Report of the Coexistence of Sickle Cell Disease, Neurofibromatosis Type 1, and Intracranial Hypertension in a Pediatric Patient. Issue 3 (3rd March 2023) - Patel, Amie; Winter, Timothy; Jain, Akshat
Abstract : A pediatric female with sickle cell disease (SCD) and neurofibromatosis type 1 was noted to have incidental papilledema, with subsequent workup showing an elevated opening pressure. She was diagnosed with intracranial hypertension and began treatment with acetazolamide. Hydroxyurea was also discontinued. Acetazolamide was tapered off, and hydroxyurea was restarted with no worsening in her ophthalmologic exam. We report this case due to the rare occurrence of all 3 conditions, and while intracranial hypertension has been reported in SCD, the diagnostic workup for papilledema in hemoglobinopathies is not well defined. This case helps delineate the presentation and diagnostic workup of papilledema in SCD.